Analysis of the Effect of Marketing Mix on Consumer Decisions to Use Service Services at Anugerah Perdana Palu Official Workshop - Leopold Merik; Nasrulhak Akkas; Guasmin Guasmin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
This study aims to see whether there is a relationship between the independent variables, namely the marketing mix including product, price, promotion, location, people/HR, physical evidence, and processes, and the dependent, namely the consumer decision at Bengkel Anugerah Perdana Monginsidi Palu. Using multiple regression analysis techniques. "In this study, for a population of 11,147, people and samples obtained by the 'incidental sampling method are 99 people." This study has seven variables, namely product, price, promotion, location, people/HR, physical evidence, and processes for the independent variable (X)" and consumer decisions as to the dependent variable (Y)." The results contained in this test are simultaneously the marketing mix consisting of product, price, promotion, location, people/ Human resources, physical evidence, and processes have a significant effect on consumer decisions with count 784.106 with 0.000, whereas partially the marketing mix consisting of product, price, promotion, location, people/HR has a positive and significant effect on physical evidence, and the process has no significant effect. The coefficient of determination (r2) in this study was 0.775 at a significant level of 0.05. It can be interpreted that 77.5% of consumer decisions at the Anugerah Perdana Monginsidi workshop in Palu are affected by the seven marketing mix variables, namely product, price, promotion, location, physical evidence, pouring/HR, and process, for 22.5% p is influenced by variables that are not examined carefully.*